A Rare Case of Tolosa-Hunt-Like Syndrome in a Poorly Controlled Diabetes Mellitus - Glenmore Lasam; Sakshi Kapur (Case Reports in Medicine)
We report a case of a 50-year-old female with diabetes mellitus who presented with progressive second, third, fifth, sixth, and eighth cranial nerve palsy. Diagnostic investigation revealed hyperglycemic state, and brain imaging showed a right cavernous sinus enhancement suggestive of and consistent with Tolosa-Hunt syndrome. The patient was started on steroids with tight glycemic control for eight weeks; subsequently, the cranial nerve palsies resolved as well as documented resolution of the right cavernous sinus enhancement.